MENINGKATKAN KECERDASAN EMOSIONAL MELALUI BIMBINGAN KELOMPOK PADA PESERTA DIDIK KELAS XI IPS 5 SMA NEGERI 1 SUNGAI RAYA TAHUN 2019/2020 - Oktavianti Oktavianti; Indri Astuti; Luhur Wicaksono (Universitas Tanjungpura, 2020)
AbstractIn addition to intellectual intelligence that must be mastered by individuals, intelligence is very important to master. In this case, if a person can master emotional intelligence, he can develop the ability to understand his own feelings, other people's feelings, and be able to motivate himself and others. The general problem in this research is: “Whether group guidance can improve students' emotional intelligence. While the intelligence sub-problem:(1) How is intelligence intelligence in students before group guidance is carried out, (2) How is group guidance planning to improve students 'emotional intelligence, (3) How is the implementation of group guidance to improve students' emotional intelligence, (4) ) How is the emotional intelligence of students after group guidance is implemented. The variables in the study consisted of problem variables: Emotional Intelligence, action variables: Group Guidance, 7 participants who had moderate levels of emotional intelligence with 5 aspects were (1) Recognizing self-emotions, (2) Managing emotions, (3) Motivating self, (4) Recognizing other people's emotions, (5) Building relationships with others. The method used is descriptive method and the form of the research is Counseling Guidance Action Research. The data collection technique used interviews and questionnaires, while the data analysis technique used the proportion formula and the T-Test formula. Keywords: Emotional Intelligence, Group Guidance, Increase.